(untitled) (Boca Raton, FL, 2010)
This book describes determining pesticide residues on food for human consumption.The fist group of chapters reviews methods and problems in analyzing pesticide residues, and looks at the scope and limitations of neem and other natural botanicals for plant protection. The next section describes in detail such methods as supercritical fluid chromatography, disposable electrochemical biosensors for environmental analysis, planar chromatography, pressurized liquid extraction, and chemiluminescence detection. Part III covers medicinal plants and pesticide residues, sample preparation and quantification, and analysis of pesticide residues in milk, eggs, and meat, fruits and vegetables, fish and wildlife, human blood and urine, animal feed, and soils
Keywords: Pesticide residues in food,Pesticides,Agricultural chemicals,Dư lượng thuốc trừ sâu trong thực phẩm,Thuốc trừ sâu,Hóa nông; Analysis,Analysis,Analysis,Phân tích,Phân tích,Phân tích